METHODS FOR TOPONIMIC RESEARCH OF OBJECTS - Seitniyazov, Q.M.; Baltabaev, O.O. (FAN va JAMIYAT, 2020)
The article is devoted to the description of toponymic research methods of geographic objects. The general concept of the methods of toponymic research, research methods of toponymy, are analyzed as well as the use of scientific and practical data in toponymic research.